2014
DOI: 10.1007/s10554-014-0501-1
|View full text |Cite
|
Sign up to set email alerts
|

Substantial iodine volume load reduction in CT angiography with dual-energy imaging: insights from a pilot randomized study

Abstract: We explored whether dual-energy computed tomography (DECT) can allow a significant reduction in iodinated contrast volume during computed tomography angiography (CTA) without hampering image quality or assessibility. We prospectively randomized patients clinically referred to CTA to single energy computed tomography (SECT) with full iodine volume load (group A), DECT with 50 % iodine volume load (group B), DECT with 40 % iodine volume load (group C), and DECT with 30 % iodine volume load (group D); and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…As expected, among the DE group, myocardial SD levels were highest at low energy levels, with significantly lower SD levels at increasing energy levels. In turn, myocardial signal-to-noise ratio was not significantly influenced by the energy level applied given that the energy level is inversely related to both SD and noise [22]. Furthermore, in line with a previous study involving conventional SE imaging, mild regional differences regarding myocardial SD levels were observed and should therefore be accounted for in order to avoid misinterpretation of the results.…”
Section: Myocardial Sd Levels Using De Imagingsupporting
confidence: 75%
“…As expected, among the DE group, myocardial SD levels were highest at low energy levels, with significantly lower SD levels at increasing energy levels. In turn, myocardial signal-to-noise ratio was not significantly influenced by the energy level applied given that the energy level is inversely related to both SD and noise [22]. Furthermore, in line with a previous study involving conventional SE imaging, mild regional differences regarding myocardial SD levels were observed and should therefore be accounted for in order to avoid misinterpretation of the results.…”
Section: Myocardial Sd Levels Using De Imagingsupporting
confidence: 75%
“…Several studies demonstrated that CIN incidence is related to the administered iodine load, which motivates the aim for the reduction of the total iodine dose (TID) [16]. In CT contrast studies, image quality largely depends on the contrast between enhanced and nonenhanced regions; hence a sufficient amount of contrast agent must be administered to the patient to assure a certain image quality.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this was accomplished despite a more than 50% reduction in iodine load for CT angiography with DECT. Similarly, a recently published study revealed that monochromatic images at 50–60 keV allow for a iodine volume reduction up to 60% without compromising image quality as reflected by similar contrast- and signal-to-noise ratios as those obtained with standard CCTA using full iodine load (68). …”
Section: Iodinated-contrast Dose Requirementsmentioning
confidence: 79%